Strategic group formation in agent-based simulation. (March 2018) - Collins, Andrew J.; Frydenlund, Erika
Researchers tend to model people as individuals rather than as members of groups. This approach diminishes the impact of altruism and other group-supporting behaviors. For example, walkers may move slower than their capability to retain group cohesion. Current modeling approaches to capture group formation and dynamics lack the strategic elements required to model the complexity of human decision-making. Game theory provides a mechanism to introduce this strategic behavior. This article investigates strategic group formation through the introduction of cooperative game theory techniques into an agent-based model and simulation (ABMS). It shows some empirical results from this introduction. The approach requires looking at the Core instead of the more common Nash Equilibrium. The simulation outputs show some agents forming a large dominant group, much like a real-world mob. The model and results are relevant to policymakers trying to understand how humans navigate an environment through strategic social interactions.